Strategic planning for the New York apple industry - Gerald B. White (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2001)
The author was involved in strategic planning for the New York apple industry, a process that began in the Spring of 2000. The industry was beset by negative economic performance resulting from a series of factors such as a world over-supply of apples in relation to demand; depressed prices for apples utilized for juice due to the effects of China selling apple juice concentrate (AJC) at prices below the cost of production; severe weather events such as hail storms in 1998 and 2000; and increasing concentration in the retailing sector that constrained access to markets in major retail chains. The combination of these events led to four consecutive years of declining prices that had the effect of reducing growers` equity and placing perhaps 20 per cent of the state's approximately 700 apple growers in vulnerable positions for survival. The extreme economic hardship faced by growers signaled clearly to industry leaders that major changes were needed for the industry to survive and prosper in the future.
Keywords: 330